ETIKA PROFESI GURU DI ERA DIGITAL: PERAN STRATEGIS SATUAN PENDIDIKAN DALAM PERSPEKTIF LITERATUR - Lu'lu 'Aabidah; Rizqi Nur Amalya; Siti Anisa Al Maulani; Faridatul Ulya; Ma’mun Hanif (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This article aims to examine teacher professional ethics in the digital era and the strategic role of educational institutions in supporting its implementation. This research uses a literature review method with a qualitative descriptive approach through a review of journal articles, books, and relevant scientific documents. The results of the study indicate that teacher professional ethics is a crucial foundation for maintaining teacher integrity, responsibility, honesty, and professionalism amidst the digital transformation. Technological developments provide significant opportunities for improving the quality of learning, but also give rise to ethical challenges, such as the misuse of social media, violations of student privacy, plagiarism, the spread of hoaxes, and the use of artificial intelligence, which has the potential to compromise academic integrity. Educational institutions play a strategic role through the development of digital policies and codes of ethics, supervision and guidance on technology use, the creation of an ethical school culture, and ongoing professional development. This study emphasizes that synergy between teachers and educational institutions is crucial for realizing professionalism that is adaptive, imbued with integrity, and relevant to the demands of the digital era.